A method for the further assembly of targeted unigenes in a transcriptome after assembly by Trinity - Xiao, Xinlong; Ma, Jinbiao; Sun, Yufang; Yao, Yinan (Frontiers in Plant Science, 2015)
RNA-sequencing has been widely used to obtain high throughput transcriptome sequences in various species, but the assembly of a full set of complete transcripts is still a significant challenge. Judging by the number of expected transcripts and assembled unigenes in a transcriptome library, we believe that some unigenes could be reassembled. In this study, using the nitrate transporter (NRT) gene family and phosphate transporter (PHT) gene family in Salicornia europaea as examples, we introduced an approach to further assemble unigenes found in transcriptome libraries which had been previously generated by Trinity. To find the unigenes of a particular transcript that contained gaps, we respectively selected 16 NRT candidate unigene pairs and 12 PHT candidate unigene pairs for which the two unigenes had the same annotations, the same expression patterns among various RNA-seq samples, and different positions of the proteins coded as mapped to a reference protein. To fill a gap between the two unigenes, PCR was performed using primers that mapped to the two unigenes and the PCR products were sequenced, which demonstrated that 5 unigene pairs of NRT and 3 unigene pairs of PHT could be reassembled when the gaps were filled using the corresponding PCR product sequences. This fast and simple method will reduce the redundancy of targeted unigenes and allow acquisition of complete coding sequences (CDS).